Exploring the Ethical Use of Artificial Intelligence in Academic Activities: A Qualitative Study of Guinean Students - Amadou Diallo; Driana Leniwati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
The rapid integration of artificial intelligence (AI) in academic contexts has raised ethical concerns around academic integrity, plagiarism, data privacy, and responsible use, with little attention given to low-resource contexts such as West Africa. The study explores ethical concerns, student experiences, and the role of sociocultural and institutional environments in guiding students' choices related to the use of AI.The methodology of this study was Interpretive Phenomenological Design (IPD) to collect the data by semi-structured interviews in French on WhatsApp and Google Meet with 10 students who have experience in using academic AI tools, and then the data was analyzed by manual thematic coding. Two main attitudes were identified: supportive-use attitude (AI as a learning tool) and independence-preserving attitude (strengthening personal efforts and originality). Students knew the ethical principles including academic honesty but were not sure what it meant when it came to paraphrasing and graded work, as a result of unclear institutional policies, limited guidance and gaps in sociocultural and infrastructural norms. The results suggest the need for more precise guidance on the use of AI along with training on ethics and assessment frameworks tailored to the Guinean context, to inform and drive institutional and policy innovations. The study finds that the use of AI in an ethical way in Guinea is not only related to students' awareness but also to coordinated institutional action, and suggests the creation of institutional frameworks for the governance of AI in the local institutions of Guinea.